Corn starch dextrin changes intestinal microbiota and its metabolic activity in rats fed a basal and high-fat diet. Issue 9 (24th July 2019) - Barczynska, Renata; Jurgoński, Adam; Slizewska, Katarzyna; Juśkiewicz, Jerzy; Kapusniak, Janusz
Abstract : Purpose: The purpose of this paper is to determine the influence of low-fat and high-fat diets supplemented with dextrin obtained from corn starch on the numbers and relative proportions of enteric bacteria Bacteroidetes ( Bacteroides, Prevotella ), Actinobacteria ( Bifidobacterium ) and Firmicutes ( Clostridium, Lactobacillus ). Moreover, basic indicators of gastrointestinal function (among other things: epidydymal fat mass, mass with contents, pH in the colon, cecum, small intestine, fecal enzymes were investigation) and short-chain fatty acids are analyzed. Design/methodology/approach: In vivo experimental studies in rats (analized samples of the ileal, cecal and colonic digesta; pH; blood serum; fecal enzymes); determination of the number of bacteria – fluorescence in situ hybridization; and determination of type and concentration SCFA – HPLC were considered. Findings: No statistically significant differences in final body weight were found between rats fed low-fat and high-fat diets supplemented with dextrin. In rats fed the low-fat diet with dextrin, the gut microbiota composition was as follows: 42.74 percent Bacteroises and Prevotella ( Bacteroidetes ), 35.28 percent Clostridium and Lactobacilllus ( Firmicutes ) and 21.98 percent Bifidobacterium ( Actinobacteria ), while in rats fed the high-fat diet with dextrin it was similar. Irrespective of the diet type, supplementation with dextrin enhances bacterial glycolytic activity and the cecal production of total SCFAs, with strongly increased propionate and decreased butyrate fermentation. Practical implications: Dextrin may enrich food or be a component of functional foods. Originality/value: Dextrin from corn starch may contribute to changes in the composition of intestinal microbiota.